Infant immunity against viral infections is advanced by the placenta-dependent vertical transfer of maternal antibodies. Issue 11 (8th March 2022) - Albrecht, Marie; Pagenkemper, Mirja; Wiessner, Christian; Spohn, Michael; Lütgehetmann, Marc; Jacobsen, Henning; Gabriel, Gülsah; Zazara, Dimitra E.; Haertel, Christoph; Hecher, Kurt; Diemert, Anke; Arck, Petra Clara
Graphical abstract: Highlights: Transplacental transport of maternal IgG depends on individual placental function. Higher cord blood antibody levels against influenza A protect the offspring from respiratory illness. Revisiting maternal vaccination strategies is crucial to improve children's health. Abstract: Neonatal passive immunity, derived from transplacental transfer of IgG antibodies from mother to fetus during pregnancy, can mitigate the risk for severe infections in the early postnatal period. Understanding the placenta as the gateway organ in this process, we aimed to evaluate the influence of specific factors modulating the transplacental IgG transfer rate (TPTR) in 141 mother/neonate pairs. We further evaluated the potential health advantage elicited by maternal IgG with regard to respiratory tract infections during infancy and early childhood. Data and biological samples collected within the prospective longitudinal pregnancy cohort study PRINCE (Prenatal Identification of Children's Health) were used for these analyses. We tested IgG antibody levels against seven pathogens (measles, mumps, rubella, tetanus, diphtheria, pertussis and influenza A) by ELISA and detected seropositivity in 72.6–100% of pregnant women and in 76.3–100% of their neonates, respectively. Cord blood IgG levels reached 137–160% of levels detected in maternal blood. Strikingly, assessment of TPTR for all seven antigens highlighted that TPTR strongly depends on individual placental function. Subsequent in-depth analysis of anti-influenza A IgG revealed a link between cord blood levels and uterine perfusion, measured by uterine artery pulsatility index. Moreover, higher cord blood anti-influenza A IgG levels were associated with a significantly reduced risk for respiratory tract infections during the first six months of life, indicating a high degree of cross-reactivity and possible pathogen-agnostic effects of anti-influenza A antibodies. Taken together, our data suggest that early life immunity is modulated by maternal IgG levels and individual placental features such as perfusion. Vaccination of pregnant women, i.e. against influenza, can increase neonatal antibody levels and hereby protect against early life respiratory infections. Consequently, specific guidelines should evolve in order to safeguard neonates born from pregnancies with poorer placental capacity for vertical transfer of protective antibodies.